Behavioral Self-Regulation as a Protective Factor for Children at Risk of Reading Failure: Predicting First-Grade Reading from Kindergarten Entry Assessment (KEA) Data. Issue 7 (3rd October 2021) - Kehoe, Karen F.; McGinty, Anita S.; Williford, Amanda P.; Whittaker, Jessica V.
ABSTRACT: Research Findings : This study used data from a large-scale kindergarten entry assessment (KEA) to understand how well two state screening measures, administered at school entry, predicted the first-grade reading outcomes of a large sample of first-time kindergarteners (N=5, 480) at high risk for future reading failure. We examined young children's emergent literacy and behavioral self-regulation skills in the fall of kindergarten in relation to decoding skills in the spring of first grade. We also explored whether behavioral self-regulation moderated the effect of emergent literacy on first-grade reading outcomes. Consistent with prior research, results of multilevel regression models revealed that scalable measures of emergent literacy and behavioral self-regulation, assessed via a multidimensional KEA, positively predicted literacy outcomes in first grade, with a stronger association for emergent literacy. Additionally, school-entry behavioral self-regulation moderated the effect of children's initial emergent literacy skills on first-grade decoding, such that stronger than average behavioral self-regulation partially compensated for weak emergent literacy at school entry. Practice or Policy : Findings underscore the importance of screening young children on both academic and non-academic domains of school readiness and of seeking to understand children's risk of reading failure from multiple perspectives.